Where did it all go wrong? Implementation failure—and more—in a field experiment of procedural justice policing - MacQueen, Sarah (Journal of experimental criminology, 2017)
This paper presents the findings from a retrospective qualitative process evaluation to the Scottish Community Engagement Trial (ScotCET). The study explores the unanticipated results of a randomized field trial testing the effect of ‘procedurally just’ modes of road policing on public perceptions of police. The ScotCET intervention failed to produce the hypothesized results, producing instead significant, and unexplained, negative effects on key aspects of public perception. The present study seeks to examine, from the perspectives of officers implementing the experiment, what the impacts (intended or otherwise) of participation were.